Ciclos e sucesso escolar: questões teóricas e práticas - Kaneko, Sidineia Muniz (2008)
This research has had the aims to investigate what is understood as achieving educational success in the vision of teachers, parents and students, and discuss the proposal of evaluation of the cycles in the Municipal School of Niterói, RJ, Professor Marcos Waldemar de Freitas Reis, approaching the reorganization of the time and of the school space, including the Rearrangement of the students, and its condition to contribute, or not, to the educational success of the students. The investigation was held in the cited school, which offers the 1st segment of Fundamental Teaching, therefore, 1st and 2nd cycles. The methodological procedures were oriented by the participant observation of the researcher, favored by her work as Educational Tutor of the school and by the opportunity of analyzing possible interfaces between the organization in cycles and the educational success achieved by the students. The social representations shared by the students, education professionals and parents have subsided the analyses. In the fundamentals, we have included the indexes of evasion and failure in the beginning school years, in Brazil, the role of the public school in face of the paradigm of the school that is a reproduction of the social classes and of the learning cycles. In the results of the analyses, we have observed that the organization of the school in cycles can be translated in educational success for the students. However, the dialogue between the theories and practices and the collective work a necessary at its implementation.